World Pizza - Cece Meng (New York, United States Sterling Publishing Co Inc, 2017)
When Momma spots a wishing star, she starts to ask for world peace - but a sneeze garbles her wish, changing "peace" into "peace-AH-AH-AH...choo!" World Pizza! Suddenly, yummy pies of every kind come drifting down from the sky. That's not exactly what Momma hoped for - or is it? With humour, warmth and heart, this delicious picture book celebrates the things that truly bring us together.
Keywords: Circle Time -- Circle Time; Relationships / Teamwork /Conflict Resolution -- Relationships / Teamwork /Conflict Resolution